Preliminary study of depth of interaction measurement for a PET detector - 廖燕飞 章志明 李道武 帅磊 单保慈 黄先超 刘军辉 陈研 王英杰 刘双全 王培林 魏书军 魏龙 (Chinese physics C, 2011)
In this work we studied the feasibility of detecting the depth of interaction （DOI） with two layers of crystal arrays of LYSO and BGO scintillators coupled to a position-sensitive photomultiplier tube （PS-PMT） R8900-C12. A front-end electronics was designed, with which we got different pulse shapes for different crystals to obtain depth information. With the double integration method, we got the DOI histogram of a divided integration ratio of two crystals as the standard to determine the layer-of-interaction. The DOI accuracy, measured by scanning a 22Na slit source along the side of the module, was 98% for the LYSO layer and 95% for the BGO layer. The energy resolution at 511keV was 13.1% for LYSO and 17.1% for BGO. We obtained good crystal separation in 2D position histograms of both layers. These results could be useful in the manufacture of PET scanners with high spatial resolutions.